ANALISIS EFEKTIVITAS PENGENDALIAN INTERN PIUTANG USAHA PADA PERUSAHAAN JASA PEMBIAYAAN - Anggi Arista (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The company implements a strategy by selling on credit to earn profits, thereby resulting in receivables. Good management of accounts receivable will generate profits for the company and the company's assets can be protected. Considering that credit is a current asset, an internal control system is needed for accounts receivable, so that the company avoids the risk of loss due to uncollectible accounts and the procedure for granting credit can run well. This study aims to analyze the effectiveness of internal control of accounts receivable in accordance with COSO principles and to provide recommendations for internal control in accordance with COSO principles at PT Kresna Reksa Finance Balikpapan Area. The research method used is qualitative with a case study approach. Data collection methods through interviews, documentation and observation.The results of this study indicate that PT Kresna Reksa Finance Balikpapan Regional Office has implemented a fairly good internal control of accounts receivable, but it is less effective because there are weaknesses in the control environment component related to the division of tasks and responsibilities for each function. The weakness lies in the absence of segregation of duties that occurs between the administration and cashiers in aspects of credit granting procedures and there is no segregation of duties between the Account Officer Survey (AO Survey) and the receivables collection section. This shows the implementation of the company's organizational structure which is still very simple when compared to the organizational structure of the company's SOP which is relatively complex.